2020
DOI: 10.1016/j.psj.2020.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing yeast fermentate in the feed or drinking water on stress susceptibility, plasma chemistry, cytokine levels, antioxidant status, and stress- and immune-related gene expression of broiler chickens

Abstract: This study aimed to elucidate the mechanism by which adding Saccharomyces cerevisiae –derived yeast fermentate to the feed ( XPC ) or drinking water reduces stress in poultry. Day-old male Cobb 500 broiler chicks were assigned to 1 of 3 treatments: stressed control ( CS ), stressed + XPC (1.25 kg/metric ton feed, day 0–43; XPC), or stressed + AviCare (160 mL/100 L drinking water, day 0–43; AVI). All birds were spray-vaccinated for coccidiosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This effect enhances the ability of poultry to handle stress and infectious agents. In another study [ 10 ], the authors investigated the mechanism by which SC enhances the oxidative status of broiler chickens. The authors included SC in either the feed or drinking water of stressed broilers and measured CYP1A2 and melanocortin-2 receptor (MC2R) gene expression in the adrenal glands and IL10 and AvBD1 in the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect enhances the ability of poultry to handle stress and infectious agents. In another study [ 10 ], the authors investigated the mechanism by which SC enhances the oxidative status of broiler chickens. The authors included SC in either the feed or drinking water of stressed broilers and measured CYP1A2 and melanocortin-2 receptor (MC2R) gene expression in the adrenal glands and IL10 and AvBD1 in the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that using SC in broilers’ feed or drinking water for 40 days decreased stress and MC2R gene expression. They also showed that supplementation of SC fermentate in the feed was marginally more effective than adding it to drinking water in stimulating oxidative status and reducing stress in broiler chickens [ 10 ] and in detoxifying nitrate (21, 22) and aflatoxin (22, 23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could be related to the fact that the Cr‐yeast is produced by culturing yeast cells in a trivalent Cr‐containing medium. Yeast may have positive effects on the regulation of inflammatory processes 41 …”
Section: Discussionmentioning
confidence: 99%
“…A likely mechanism associated with XPC is rooted in the demonstrated changes to the microbiota in response to XPC supplementation, shifting the metabolites present, and ultimately reducing Salmonella fitness (Park et al, 2017;Rubinelli et al, 2016;Feye et al, 2019). The same mechanism likely drives the immune-modulating response that reduces peripheral inflammation while increasing the phagocytosis of Salmonella (Feye et al, 2016b(Feye et al, , 2019Nelson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%